2000
DOI: 10.1111/1467-6494.00133
|View full text |Cite
|
Sign up to set email alerts
|

Personality Psychology and Problem Behaviors: HIV Risk and the Five‐Factor Model

Abstract: Studies of personality and problem behaviors may begin with analyses of the problem and develop hypotheses about personality traits that might be relevant; or they may begin with models of personality and explore links to behavior. Because it is well validated and relatively comprehensive, the Five-Factor Model (FFM) of personality lends itself to systematic exploratory studies that may sometimes lead to unanticipated findings. In this article, we review a program of research in a high-risk, disadvantaged popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 27 publications
2
66
0
Order By: Relevance
“…It is possible that when faced with HIV, these "experience seekers" might be more proactive and seek out information that might afford them some advantage in managing their disease. These results are broadly consistent with an earlier study that found high Openness is related to more realistic HIV risk estimates (39). In this sample, NEO-PI-R Openness is significantly correlated with the items: "I ask my doctor about new treatments and new research" (r = .20, p = .016) and with "I read up on my own about new medications and new treatments" (r = .25, p = .003).…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that when faced with HIV, these "experience seekers" might be more proactive and seek out information that might afford them some advantage in managing their disease. These results are broadly consistent with an earlier study that found high Openness is related to more realistic HIV risk estimates (39). In this sample, NEO-PI-R Openness is significantly correlated with the items: "I ask my doctor about new treatments and new research" (r = .20, p = .016) and with "I read up on my own about new medications and new treatments" (r = .25, p = .003).…”
Section: Discussionsupporting
confidence: 92%
“…Given these data, it would be appropriate to mention the skeptical claims concerning traits theories in which authors such as Caprara and Cervone or Borsboom, Mellenbergh and Van Heerden are an example (68,69). These perspectives were Agreeableness appears as a protective variable in its high-rank and as a risk factor in its low-rank (54,55,60). In the same works, these facets appear related to lower condom use, increased frequency of couples, drug use in the context of sex or infidelity.…”
Section: Insert Table IImentioning
confidence: 99%
“…On the other hand, it is also expected that the personality variables associated with risky sexual behavior (high Neuroticism and low Conscientiousness) may have a negative influence on this behavior (55). Regarding the influence of emotional factors, a recent study noted high levels of anxiety, depression and distress in people who were tested voluntarily (56).…”
mentioning
confidence: 99%
“…While individuals who are high in conscientiousness are less likely to engage in risky behaviors associated with long-term negative consequences [21,24,25], they also tend to believe that they are less susceptible to health risks [26]. However, those who are high in conscientiousness have been found to expend greater effort when seeking information [18] and to draw on a larger proportion of available information when solving problems [27].…”
Section: Introductionmentioning
confidence: 99%
“…The RISP model would suggest that this effect on health information seeking may be partially mediated by risk perceptions. For example, Trobst et al [25] found that openness to experience had a positive association with perceived risk of testing positive to HIV. In discussing this association, the authors reasoned that people who are open to experience may have been both more likely to engage in behaviors that put them at greater objective health risk and to have sought out information that would make them aware of that risk.…”
Section: Introductionmentioning
confidence: 99%